Impact of blastocyst biopsy for preimplantation genetic testing on maternal and neonatal outcomes following single frozen embryo transfer cycles - Tingting He; Wenhao Shi; Xia Xue; Juanzi Shi (BMC Pregnancy and Childbirth)
Abstract Background Up to now, a number of studies have explored the influence of blastocyst biopsy on maternal and neonatal outcomes, and the results have been somewhat inconsistent. Therefore, the aim of this study was to investigate whether blastocyst biopsy is associated with an elevated risk of hypertensive disorders of pregnancy (HDP) and other adverse perinatal outcomes during frozen embryo transfer (FET) cycles in singleton live births resulting from intracytoplasmic sperm injection (ICSI) in women aged ≤ 35 years. Methods A total of 1,008 women were involved in this study from January 2020 to June 2022, who underwent ICSI cycles and received single FET, leading to the birth of a live singleton newborn. The study population were categorized into two groups: the preimplantation genetic testing (PGT) group, comprising 269 women whose blastocysts underwent trophectoderm biopsy, and the control group, consisting of 739 women whose blastocysts did not undergo biopsy. The primary outcome assessed in this study was HDP. Additionally, various relevant perinatal outcomes related to both maternal and neonatal health were also evaluated. Results In comparison to the control group, notable disparities were observed between the groups in relation to infertility duration, EMT, infertility type, infertility cause and endometrial preparation protocol (P < 0.05, for all). The percentage of female gender significantly increased in the PGT group in comparison with the control group (P < 0.05). However, the risk of HDP, other maternal and neonatal outcomes exhibited comparable results between the two groups (P > 0.05, for all). Moreover, univariate regression analyses further revealed that PGT had no influence on maternal and neonatal outcomes, except for gender (aOR 1.44; 95% CI, 1.03–2.01; P = 0.031). Conclusions In the short-term perspective, it could be inferred that blastocyst biopsy may not increase the risks associated with HDP or other unfavorable maternal and neonatal outcomes. However, despite the limited sample size, our findings may not be applicable to those aged 35 or over; therefore, larger cohort studies are imperative for the validation of our results.